Domestic Violence Offender Treatment and Multidisciplinary Treatment Teams: The Role of "Treatment" Victim Advocates. (March 2018) - Richards, Tara N.; Gover, Angela R.
In Colorado, "treatment victim advocates" (TVAs) serve alongside providers and probation/parole officers on "multidisciplinary treatment teams" (MTTs) to oversee domestic violence offender's treatment. Although this model provides an opportunity for victim safety concerns to be heard, the utility of using victim advocates as advisors regarding interventions for domestic violence offenders has yet to be studied. Using survey data and narrative responses from TVAs ( N = 37), the current study examines the challenges and opportunities TVAs face while serving on MTTs. Results suggest that, overall, TVAs are successful in communicating with other members of the MTT, are confident that their perspectives are valued in the offender decision-making process, and are able to provide a wide variety of services and referrals to the victims with whom they are engaged. Implications and recommendations for the Colorado model as well as correctional professionals managing domestic violence offenders internationally are presented and discussed.